COMPARATIVE ANALYSIS OF FULMER, SPRINGATE AND GROVER MODELS IN PREDICTING BANKRUPTCY - Rahma Yudi Astuti (Journal of Islamic Economics and Philanthropy, 2021)
This study aims to determine the difference in scores between the Fulmer, Springate and Grover models in predicting bankruptcy and to determine the model with the highest level of accuracy in the property and real estate industry listed on the Indonesian Sharia Stock Index (ISSI). Bankruptcy prediction needs to be done because an analysis is very important for companies in determining decisions. This study uses secondary data obtained from financial statements listed on the Indonesia Stock Exchange (IDX). The sampling technique uses purposive sampling so that 40 companies are sampled. The analytical technique used in this research is Kruskall Wallis non-parametric analysis and test the accuracy of the prediction model. The results of this study indicate that there are significant differences between the Fulmer, Springate and Grover models in predicting the bankruptcy of the property and real estate industries. The Fulmer model is the most accurate model with an accuracy rate of 80%, a type I error rate of 70% and an error II type 3%.